Nonmetallic metal toward a pressure-induced bad-metal state in two-dimensional Cu3LiRu2O6. Issue 2 (6th December 2019) - Huang, Bin; Liu, Ziyi; Han, Yifeng; Zhao, Shuang; Wu, Meixia; Frank, Corey E.; Greenblatt, Martha; Croft, Mark; Quackenbush, Nicholas F.; Liu, Sizhan; Tyson, Trevor A.; Zhang, Lei; et al.
Abstract : The two-dimensional honeycomb layered nonmetallic metal Cu3 LiRu2 O6 exhibits Pauli-like paramagnetic and Mott variable range hopping semiconduction behaviors, which can be significantly suppressed toward a bad-metal state by pressure up to 35 GPa. Abstract : The novel two-dimensional honeycomb layered Cu3 LiRu2 O6 exhibits Pauli-like paramagnetic and Mott variable range hopping semiconduction behaviors, which contradict the large specific-heat Sommerfeld coefficient for metals, and indicate a possible spin-excitation induced nonmetallic metal. This nonmetallic feature can be significantly suppressed by pressure toward producing a bad-metal state, as reflected by the temperature-dependent resistivity response up to 35 GPa.